OPTIMAL DISTRIBUTION NETWORK RECONFIGURATION FOR LOSS MINIMIZATION AND VOLTAGE PROFILE IMPROVEMENT BASED ON ARTIFICIAL INTELLIGENCE - Omar Muhammed Neda (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
Optimal reconfiguration is a significant alternative technique of increasing the efficacy of Radial Distribution Networks (RDNs). Reconfiguration is carried out by adjusting the status of RDN switches in such manner that the system's radiality is kept, energized wholly loads and other restrictions are fulfilled. The original version of the Dolphin Echolocation Optimization (DEO) algorithm is designed for solving continuous optimization issues only. As the reconfiguration problem is a discrete issue, the original DEO algorithm cannot deal with this problem. Fortunately, a Binary DEO (BDEO) algorithm was presented for solving discrete optimization issues which is utilized for adapting the reconfiguration issue. This approach is a powerful tool for rearranging systems by altering the status of the RDN switches in a way that minimizes power loss and enhances voltage profile. The BDEO algorithm is evaluated on an IEEE 33 bus RDN under three case studies in MATLAB to validate its performance. By comparing the simulation results with those from previously published work, it is possible to conclude that the suggested strategy is efficient in achieving the optimal outcome because it enhances the system voltage profile while minimizing losses. The comparison results showed that, in instance two, the BDEO for the test RDN greatly increased the minimum voltage from 0.9131 to 0.9431 P.U. and reduced the power loss by 34.2%, from 202.67 to 133.17 KW.